Masculinos em mutação: a performance drag queen em Fortaleza - Gadelha, José Juliano Barbosa (2009)
This dissertation shows how the drag queen experience present in the city of Fortaleza, located in the Northeastern region of Brazil, consists of a ritualistic and performative experience which challenges the limits of the binary of gender and sex and also narrows what we understand as the world of arts and the everyday life. The field research is based on direct observations in the places where the drag queen performances happen in Fortaleza such as nightclubs, bars and other cabaret entertainment clubs, as well as on the collection of data in more than 50 interviews in life-story model recorded between the years 2004 and 2007 with drag queens, transformists, transsexuals and transvestites in this city. The ritualistic and performative aspects of the drag queen experience is evidenced through an analysis of what these characters name “montagem” (cross-dressing), the author can conclude that an becoming-artist can be found by the drag queens in the form of certain liminalities. The theoretical scope of this work is based on the anthropology of the ritual, the ethno-aesthetics, the Performance Studies, the Queer Theory and the sociology of agency. The methodology follows the steps of a meta-etnography in dialogue with the cartography experience, developed by Gilles Deleuze and Félix Guattari.